2014
DOI: 10.1073/pnas.1420167111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of distracting faces on visual selective attention in the monkey

Abstract: In primates, visual stimuli with social and emotional content tend to attract attention. Attention might be captured through rapid, automatic, subcortical processing or guided by slower, more voluntary cortical processing. Here we examined whether irrelevant faces with varied emotional expressions interfere with a covert attention task in macaque monkeys. In the task, the monkeys monitored a target grating in the periphery for a subtle color change while ignoring distracters that included faces appearing elsew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 66 publications
5
24
0
Order By: Relevance
“…In contrast, this source of competition is removed in the covert task (since only a single stimulus was presented). Indeed, unattended task-irrelevant peripheral faces can impair performance in a variety of settings (Landman et al, 2014) and it is possible that the reduction of selectivity we observed here is a reason for this effect.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, this source of competition is removed in the covert task (since only a single stimulus was presented). Indeed, unattended task-irrelevant peripheral faces can impair performance in a variety of settings (Landman et al, 2014) and it is possible that the reduction of selectivity we observed here is a reason for this effect.…”
Section: Discussionmentioning
confidence: 81%
“…Given the similarities between monkeys and humans in the neural circuitry underlying social cognition (19), the rhesus macaque could be an ideal animal model to examine the effects of OT. To date, only a few studies have investigated the behavioral consequences of OT administration in monkeys (20)(21)(22)(23)(24)(25). Consistent with the human literature, these studies have found that intranasal administration of OT affects social behavior and cognition in monkeys, Significance Oxytocin (OT), a mammalian hormone, may serve as a treatment for psychiatric disorders because of its beneficial effect on social behavior.…”
mentioning
confidence: 83%
“…Emotional stimuli, both negative and positive emotion, tend to attract attention in humans as well as other primates [2126]. However, there is a critical distinction between the perceptual correlates of negative and positive emotions, with negative emotion narrowing and positive emotion broadening the scope of attention or perception [2730].…”
Section: Introductionmentioning
confidence: 99%